Potential Sources of Raw Water in Coastal Areas, Jawai and South Jawai Districts, Sambas Regency, West Kalimantan - Samiat Samiat; Nora Idiawati; Sepridawati Siregar; Sukal Minsas (Jurnal Ilmu Lingkungan, 2025)
The coastal areas of Jawai and South Jawai Districts are located in Sambas Regency, Pontianak, West Kalimantan, which have limited access to clean water needs, especially for drinking water needs. This research was conducted in several villages in Jawai District and South Jawai District. Samples taken from the village were rainwater, drilled well water, mountain water, shallow well water, and ditch water, which were then analyzed for chemical, physical, and microbiological parameters. The research aims to determine the potential of raw water sources in the Jawai and South Jawai sub-districts to fulfill the need for clean water and drinking water based on the Decree of the Minister of Health of the Republic of Indonesia Number 2, 2023, concerning environmental health quality standards for drinking water media and water use designations based on the Government of the Republic of Indonesia No. 82, 2001, concerning Water Quality Management and Water Pollution Control. Based on Government Regulation no. 82, 2001, from the results of water analysis in Jawai District, only rainwater has values that are still ≤ parameter quality standards, while in South Jawai District, mountain water and rainwater have values that are still ≤ parameter quality standards. Therefore, this water source is included in the category of first-class water, namely water whose designation can be used for raw drinking water and other purposes that require the same water quality as that use. Based on the Republic of Indonesia Minister of Health Regulation No. 2, 2023, rainwater, mountain water, and drilled well water are unsuitable for drinking water use. Based on the STORET method, the water quality status is included in class B, namely the 'lightly polluted' category.